How does ambidextrous leadership promote innovation in project-based construction companies? Through mediating role of knowledge-sharing and moderating role of innovativeness - Haider, S. A.; Zubair, M.; Tehseen, Shehnaz *; Iqbal, S.; Mariam, S. (Emerald, 2021)
Purpose: Research on adopting leadership style like ambidextrous leadership to enhance employees' innovative work behavior (IWB) is in an initial stage. Moreover, employees need a high knowledge sharing attitude to show more IWB. The purpose of this study is to empirically test the impact of ambidextrous leadership on IWB with the mediating role of knowledge sharing and the moderating role of innovativeness as a project requirement (IAPR). Design/methodology/approach: The simple random sampling technique was used to collect data from 542 employees of project-based construction companies operating in Pakistan. Smart partial least squares-structural equation modeling (Smart PLS SEM v.3.2.8) was used to test the hypotheses. Findings: The result revealed that ambidextrous leadership has a significant and positive effect on knowledge sharing but negative effect on IWB at the workplace. Additionally, the mediating role of knowledge sharing has been tested and proved to be a potential mediator between ambidextrous leadership and IWB. Also, IAPR as moderator has a significant and positive effect on knowledge sharing and IWB. Practical implications: The managers need to develop an ambidexterity-oriented strategy and communicate this strategy across the members of the whole organization. These processes can be facilitated by ambidextrous leaders with complex behavioral repertoires and specific constellations and characteristics of top management teams. Originality/value: The relationship between ambidextrous leadership and IWB is the new contribution through the mediating of knowledge sharing between AL and IWB also moderation role IWB between knowledge sharing and IWB.